2005
DOI: 10.1002/jat.1093
|View full text |Cite
|
Sign up to set email alerts
|

Pro-oxidative vs antioxidative properties of ascorbic acid in chromium(VI)-induced damage: anin vivo andin vitro approach

Abstract: The effect of antioxidant ascorbic acid (vitamin C) pretreatment on chromium(VI)-induced damage was investigated using the yeast Saccharomyces cerevisiae as a model organism. The objective of this study was to pretreat yeast cells with the antioxidant ascorbic acid in an effort to increase cell tolerance against reactive chromium intermediates and reactive oxygen species formed during chromium(VI) reduction. Intracellular oxidation was estimated using the fluorescence indicators dihidro-2,7-dichlorofluorescein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 80 publications
0
46
0
Order By: Relevance
“…However, the compounds which act as antioxidants should have redox cycling character (the ability to undergo reduction and oxidation repeatedly) to reduce free radicals. Vitamins react with ROS and themselves become pro-oxidants [15]. Pro-oxidants react with superoxide to generate highly reactive hydroxyl radicals.…”
Section: Introductionmentioning
confidence: 99%
“…However, the compounds which act as antioxidants should have redox cycling character (the ability to undergo reduction and oxidation repeatedly) to reduce free radicals. Vitamins react with ROS and themselves become pro-oxidants [15]. Pro-oxidants react with superoxide to generate highly reactive hydroxyl radicals.…”
Section: Introductionmentioning
confidence: 99%
“…The modified tolerance of the mu-tant cells to chromate is accompanied with the changes in Cr(VI) uptake and chromium bioaccumulation [22]. It was shown that ascorbic acid influenced Cr(VI) toxicity both as an antioxidant, by decreasing intracellular reactive oxygen species, and as a reducing agent, by decreasing the level of Cr(V), a highly toxic intermediate in chromate reduction [23]. The effects of chromate on cell growth and lethality were studied using DNA repair-deficient S. cerevisiae mutants [24].…”
Section: Introductionmentioning
confidence: 99%
“…The defense system is present in aqueous and membrane compartments of cells and can be enzymatic or non-enzymatic. A second category of natural antioxidants involves repair processes that remove damaged biomolecules before they can accumulate and before their Vitamin C can promote metal ion-dependent hydroxyl radical formation in biological fluids Poljsak et al, 2005;Rietjens et al, 2002;Stearns et al, 1995). Burkitt and Milne (1996) also reported hydroxyl radical formation from Cu(II)-trolox mixtures.…”
Section: Introductionmentioning
confidence: 98%